Carbon footprint of dryland winter wheat under film mulching during summer-fallow season and sowing method on the Loess Plateau. (December 2018) - Xue, Jian-Fu; Yuan, Ya-Qi; Zhang, Hai-Lin; Ren, Ai-Xia; Lin, Wen; Sun, Min; Gao, Zhi-Qiang; Sun, Da-Sheng
Highlights: We accessed the effect of film mulching and sowing method on crop CF. Fertilizer was the largest contributor to the CF of dryland winter wheat. Precipitation affected largely the CF of dryland winter wheat among years. Increasing SOC sequestration can reduce the CF of dryland winter wheat. FM × DS may be a C-friendly technology for dryland winter wheat. Abstract: To identify more carbon (C)-friendly agricultural technology, we studied the coupling impact of film mulching during summer fallow and sowing method on carbon footprint (CF) of dryland winter wheat ( Triticum aestivum L.) on the Loess Plateau. From 2011 to 2014, a two-factor split block design was conducted with the following treatments: water-permeable film mulching in the summer fallow season (FM) or no mulching in the summer fallow season (FM0) with either conventional drill sowing (DS) or drill sowing beside a common film (DSF). The greenhouse gases (GHG) emissions associated with agricultural inputs were 7013.3, 5908.3, 5298.5, and 4193.5 kg CO2 -eq·ha −1 ·yr −1 for FM × DSF, FM0 × DSF, FM × DS, and FM0 × DS treatments, respectively, which contributed >80% of total GHG emissions during the winter wheat production. Fertilizer, especially P2 O5 fertilizer, was the largest contributor to GHG emissions from agricultural inputs. The CF of dryland winter wheat was 1.14 to 3.60 kg CO2 -eq kg −1, which was the lowest under the FM × DS treatment while the largest under the FM × DSF treatment. Film mulching during summer fallow with drill sowing (FM × DS) could be a C-friendly technology for winter wheat production on the Loess Plateau.